WOMEN EMPOWERMENT THROUGH MANAGEMENT OF HANDICRAFTS IN THE MAKING OF ACRYLIC BONSAI FLOWERS DURING THE PANDEMIC, IN KERINJING VILLAGE, TANJUNG RAJA DISTRICT OGAN ILIR REGENCY - Sukanto, Sukanto; Puspita Sari, Dwi Darma; Hamidi, Ichsan; Pratama Atiyatna, Dirta; Hamira, Hamira (LPPM Univ. Ibn Khaldun Bogor, 2022)
This service program aims to provide skills in the form of providing training on handicrafts through the manufacture of acrylic bonsai flowers and how to market them so that they can become souvenirs and can increase income for the people of Kerinjing Village. In addition, the product from this training is also expected to be a superior product in the countryside in Kerinjing Village. The method used in this program is carried out through several stages, including the stage of building commitment, the stage of teaching and socializing with the community, the stage of needs assessment, and the stage of planning activities and implementing activities. The results of this activity include handicraft products through the manufacture of acrylic bonsai flowers which have a selling value so that they can increase the household income of women's groups in Kerinjing Village, Tanjung Raja District. Furthermore, this product is also expected to become one of the superior products in this village.